Severe silicosis due to diatomaceous earth in dental alginate: a necropsy study: Severe silicosis due to diatomaceous earth in dental alginate: a necropsy study - Barbieri, Pietro Gino; Somigliana, Anna; Carradori, Giorgio (La Medicina del Lavoro, 2020)
Background: Severe silicosis from occupational exposure to calcined diatomaceous earth has been observed in the past, due to the high-temperature transformation of amorphous silica in crystalline phases, mainly cristobalite. In dental alginate production and use a silica exposure may be underestimated. Objectives: To describe the clinical picture, the scenario and pattern of occupational exposure to silica and the corresponding necroscopic findings of a case of silicosis in a worker engaged in the production of alginates for dental use. Methods: A commercial sample of calcinated diatomaceous earth and necroscopic lung samples were analysed by scanning electron microscopy (SEM-EDS) and X-ray diffraction (XRD) for the quali-quantitative determination of crystalline silica. Material safety data sheets (MSDSs) of diatomaceous earth produced in 2002 and 2018 were examined to assess the information content on silicosis risk. Clinical findings and post-mortem examinations of the worker are evaluated. Results: A cristobalite concentration of 36% (wt/wt) was determined in the diatomaceous earth sample and a large amount of diatom fragments were observed in lung samples. The DRX spectra indicated the presence of cristobalite either in the bulk sample or in the lung tissues. The MSDS dated 2002 reported the presence of SLC up to 63% with cristobalite concentrations <60%, and the resulting risk of silicosis, while the MSDS dated 2018 and referred to a commercial product currently on the market indicated a concentration of cristobalite <1% and no risk of silicosis. The worker was suffering from a severe silicosis, histologically confirmed by necropsy. Conclusion: The present case-study revealed that the risk of silicosis from calcined diatomaceous earths used to produce dental alginates has been ignored. The lack of engineering controls and personal protection measures led to a high cristobalite lung burden, consistent with the development of a severe silicosis that were a contributing factor of death. A MSDS of a commercial product currently on the market does not report this serious hazard.